Vietnam War heroes - Zullo, Allan (Zullo, Allan. Ten true tales., 2015)
Documents the stories of ten real-life war heroes who served in the Vietnam War, including a helicopter pilot who braves a daring rescue of dozens of severely wounded soldiers under attack by the enemy.